Statistical estimations of the number of future ozone exceedances due to climate change in Europe. Issue 12 (20th June 2013) - Varotsos, K. V.; Tombrou, M.; Giannakopoulos, C.
Abstract: [1] A statistical model to examine the potential impact of increasing future temperatures due to climate change on ozone exceedances (days with daily maximum 8 h average ≥ 60 ppb) is developed for Europe. We employ gridded observed daily maximum temperatures and hourly ozone observations from nonurban stations across Europe, together with daily maximum temperatures for 2021–2050 and 2071–2100 from three regional climate models, based on the Intergovernmental Panel on Climate Change Special Reports on Emissions Scenarios A1B scenario. A rotated principal components analysis is applied to the ozone stations yielding five principal components, which divide the study domain in five subregions. The historical ozone‐temperature relationship is examined and then used to provide estimates of future ozone exceedance days under current emissions and under the assumption that this relationship will retain its main characteristics. Results suggest that increases in the upper temperature percentiles lead to statistically significant increases (95% statistical significance level) of the ozone exceedances for both future periods. The greatest average increases depending on the particular regional climate model range from 5 to 12 extra ozone days/yr for 2021–2050 and from 16 to 25 for 2071–2100, in southeast Europe. The lowest average increases range from 0 to 2 extra ozone days/yr for 2021–2050 and from 2 to 4 for 2071–2100 and are seen in northwest Europe. The simulations with the dynamical Goddard Institute of Space Studies/GEOS‐CHEM climate chemistry modeling system shows decreases instead of increases in eastern Europe, higher increases in northwest Europe, whereas for the other subregions similar results to the statistical model are obtained. Key Points: Statistical models can complement the dynamical ones Statistical models could provide useful tools for policymakers Greatest increases of climate change impact on ozone are seen in Southern Europe